Recent advances in colorimetric and fluorescent chemosensors based on thiourea derivatives for metallic cations: A review. (September 2022) - Muhammad, Mian; Khan, Sikandar; Shehzadi, Syeda Aaliya; Gul, Zarif; Al-Saidi, Hamed M.; Waheed Kamran, Abdul; Alhumaydhi, Fahad A.
Abstract: Thiourea and its derivatives display several electronic and structural features which enable its application in various fields, ranging from biological to non-biological. These compounds contain heteroatom's like sulfur and nitrogen, which are nucleophilic and allow for establishing inter-and intramolecular hydrogen bonding. In addition, they also provide coordination sites to act as ligands in the field of coordination chemistry. Due to these properties, thiourea derivatives are used as chemosensors to detect various metal cations. This article covers a broad range of thiourea based chemosensors that are used for colorimetric and fluorimetric (turn-off and turn-on) detection of different cations such as Ag +, Zn 2+, Cd 2+, Hg 2+, Pb 2+, Mn 2+, Cu 2+, Co 2+, Al 3+, Cr 3+, Ga 3+, In 3+, Ru 3+, and Fe 3+, etc., in various biological, agricultural and environmental samples. Structural parameters and coordination mechanism of each sensor with metal ions have been discussed. Further, the sensing performances of thioureas derivatives have been compared and discussed, which could help the readers for the future design of highly sensitive and selective organic fluorescent and colorimetric chemosensors to detect metal cations. Graphical abstract: Image 1 Highlights: This article covers thiourea based chemosensors for colorimetric and fluorimetric detection of metal cations. Discuss the structural parameters and coordination mechanism of each sensor with metal ions. Compare the sensing performances of thioureas derivatives .